A three-component signaling system plays multiple roles in the pathogenicity of Xanthomonas citri subsp. citri - Xiaoyan Zhao; Xiaoyun Chen; Junjie Lei; Jiaying Feng; Yunyang Dong; Yu Shi; Linghui Xu; Junxia Wang (Phytopathology Research)
Abstract Two-component signaling systems play crucial roles in bacteria by enabling them to sense and respond to environmental changes. These systems typically consist of a sensor kinase protein and a response regulator protein. The involvement of the second messenger cyclic diguanylate monophosphate (c-di-GMP) in modulating the specificity of two-component signaling has been reported in Xanthomonas campestris pv. campestris. In this study, we investigated the role of a three-component signaling system in the plant pathogen X. citri subsp. citri (Xcc). Three mutant strains, namely, ΔXAC1991, ΔXAC1992, and ΔXAC1994, were generated in the Xcc jx-6 strain background to examine virulence traits. The subcellular localization of XAC1991, XAC1992, and XAC1994 was visualized using Leica microscopy, while the flagellar structure of each mutant strain was examined by transmission electron microscopy. Transcriptome sequencing analysis and quantitative real-time PCR validation were performed to elucidate the underlying regulatory mechanisms. Our findings revealed that extracellular polysaccharide production in the ΔXAC1991, ΔXAC1992, and ΔXAC1994 mutant strains was significantly elevated compared with that in the wild-type strain, whereas extracellular protease activity was reduced. Moreover, the swimming motility of the three mutant strains was lower than that of the wild-type strain. XAC1991 and XAC1992 were located at the bacterial cell poles, whereas XAC1994 was situated at the cell periphery. Transmission electron microscopy analysis showed the absence of flagellar structures in the ΔXAC1991, ΔXAC1992, and ΔXAC1994 mutant strains. Transcriptome sequencing and real-time quantitative PCR verification indicated that the ΔXAC1991, ΔXAC1992, and ΔXAC1994 mutant strains exhibited decreased bacterial chemotaxis and flagellar assembly. Notably, both the GGDEF and EAL domains of XAC1992 negatively regulate Xcc virulence, with the GGDEF domain playing a predominant role. Overall, our study reveals the significant role of a novel three-component signaling system in modulating the pathogenicity of Xcc.